Effectiveness of Reverse Sural Artery Flap in The Management of Wheel Spoke Injuries of the Heel - Soonhan,; Awan, Aneeq Ahmed; Almas, Danish; Qadir, Sarshaar; Noor, Sara; Ashraf, Asad (Indus Journal of Bioscience Research, 2025)
Objective: To evaluate the effectiveness and outcomes of the reverse sural artery flap (RSAF) in managing wheel spoke injuries of the heel in a tertiary care setting in Pakistan, with an emphasis on its indications, postoperative complications, and functional recovery. Study Design: Cross-sectional descriptive study. Place and Duration of Study: Department of Plastic and Reconstructive Surgery, PNS Shifa Hospital, Karachi, Pakistan, conducted between August 2024 and January 2025. Methodology: Data were collected from patients treated with RSAF for reconstructive purposes following wheel spoke injuries to the heel. The study included patient demographics, details of the injury, and postoperative outcomes. The main outcomes assessed were complications such as flap necrosis, donor site morbidity, and functional recovery, along with the success rate of RSAF in covering soft tissue defects. Data analysis was performed using SPSS Version 22, with a significance level of p-value < 0.05. Results: RSAF successfully covered heel defects in 90% of cases. In the remaining 10%, minor complications were observed, including partial flap necrosis and donor site issues like scar formation and sensory changes but there were no cases of osteomyelitis or major complications. Functional recovery was excellent, with all patients regaining weight-bearing ability within six months. The average hospital stay was 14–16 days, and follow-ups at 1, 3, and 6 months showed stable flap viability and satisfactory healing. Early intervention significantly improved outcomes, confirming the importance of timely surgery. Conclusion: The reverse sural artery flap is a viable and effective option for the reconstruction of soft tissue defects in wheel spoke injuries of the heel in the Pakistani population. The technique offers reliable coverage and good functional outcomes, with minimal complications when performed in a timely manner. The study highlights the importance of early intervention and appropriate postoperative care to optimize results.